The hypo-osmotic swelling test : an assay of cell membrane integrity and quality of frozen thawed buffalo semen - PANT, H C; MITTAL, A K; PATEL, S H; SHUKLA, H R; KASIRAJ, R; PRABHAKAR, J H (The Indian Journal of Animal Reproduction, 2023)
Frozen-thawed semen from IO buffalo bulls was subjected to hypo-osmotic swelling test (HOSn byincubating for 60 minutes at 37°C in a fructose/sodium citrate solution with an osmolarity of 100 mOsm kg-1• Onexamination with a phase-contrast microscope (x400), a proportion of cells with intact membranes were foundswollen characterized by bending, coiling or shortening of the tail. Some of these cells showed non-progressiveflickering of the middle piece. Of the 10 :bulls, one which had the lowest mean value for swollen spermatozoafollowing HOST also had the lowest fertility. It is concluded that the HOST could be useful in evaluating fertilityof buffalo bulls in conjuction with other semen analysis parameters. Further studies should involve separateassessment of both inactive and active swollen cells and their relationship to fertility.
Keywords: Hypoosmotic test; buffalo; semen quality; fertility